The system approach to a problem of increase of efficiency of onboard complexes avionics on life cycle - Воробйов, В. М.; Захарченко, В. П.; Казак, В. М.; Кічігін, А. А. (Proceedings of National Aviation University (archive), 2003)
Methodological basis of the decision of tasks of increase of efficiency of onboard complexes of air courts is the system approach, which is submitted by multilevel hierarchical structure " of a tree of the purposes " problems " Increases of reliability of complicated systems of the air equipment and final link in system of safety of flights - complex " crew - air vessel - environment". In clause is offered structurization of parameters and parameters of an estimation of efficiency of functional complexes of air courts. Use of the developed structure allows to create methodological basis for maintenance of effective realization and management of processes of designing, manufacture, certification and operation of the specified complexes